2017
DOI: 10.1016/j.eururo.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Ability of a Genomic Classifier to Predict Metastasis and Prostate Cancer-specific Mortality after Radiation or Surgery based on Needle Biopsy Specimens

Abstract: Biopsy Decipher predicted metastasis and prostate cancer-specific mortality risk from diagnostic biopsy specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…[29][30][31] The data from the current study also demonstrated a larger difference in OS compared with PCSM among these populations. Therefore, the current study data affirm NCCN guidelines indicating that caution should be applied when considering AS for men with favorable intermediate-risk disease as we await longer follow-up data regarding population-wide outcomes with AS.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[29][30][31] The data from the current study also demonstrated a larger difference in OS compared with PCSM among these populations. Therefore, the current study data affirm NCCN guidelines indicating that caution should be applied when considering AS for men with favorable intermediate-risk disease as we await longer follow-up data regarding population-wide outcomes with AS.…”
Section: Discussionsupporting
confidence: 63%
“…In the interim, multiparametric magnetic resonance imaging or biomarker testing may help to optimally select and follow patients being treated with AS to ensure that opportunity for cure is not lost in men with more aggressive disease than initial risk stratification may suggest. [29][30][31] The data from the current study also demonstrated a larger difference in OS compared with PCSM among these populations. Although these differences in OS likely are due in part to PCSM, other factors such as patient comorbidity also may have contributed.…”
Section: Discussionsupporting
confidence: 63%
“…Machine learning methods based on predictive (classification) models using RF have recently been widely applied in many diagnostic, prognostic and therapeutic studies (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Machine learning methods based on predictive (classification) models using RF have recently been widely applied in many diagnostic, prognostic and therapeutic studies (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides evidence for the clinical benefits of quantitative immunophenotyping by a rational and effective marker panel followed by the use of a predictive model (diagnostic classifier), minimizing the subjectivity of commonly used expert-based assessment. Machine learning methods based on predictive (classification) models using RF have recently been widely applied in many diagnostic, prognostic and therapeutic studies (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Hereby we also showed its utility for the evaluation of flow cytometry data.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality analysis was limited due to a low rate of PCSM. [49] These retrospective evaluations provide evidence of the utility of Decipher™ testing on prostate biopsy specimens, however there is clearly a need for further prospective evaluation.…”
Section: Currently Available Testsmentioning
confidence: 99%